INDONESIA DALAM KONSEP KENEGARAAN PERSPEKTIF ISLAM DUNIA - Khoir, Misbahul (Akademika, 2017)
Some people of Indonesian moeslem there are wanting to change Indonesian Democration System tobe Islamic State Or Khilafah system. We should know whether there is any concept of Islamic state in the al-Qurâ€™an or al-Hadith literature? As far as I know in the holy Qurâ€™an and al-Hadith point us that There is no such concept of Islamic state. Although, after our prophet Muhammad Saw died, people of Muslems was confusing at looking for a leader continueÂ  leadership in Islam, Our prophet Muhammad Saw gave a concept of a society rather than a state and in the al-Qurâ€™an had been explaned ( â€˜adil /justice and ihsan). One of state form is like confederacy (in America) but in Indonesia state is â€˜teo-demokrasiâ€™ with united identification: (1)The supreme of the central parliament; (2) The absence of subsidiary sovereign bodies; Islamic is away of life (syariâ€™at) thereâ€™s no have a permanent concept about state. For example, Khilafah system and etc. Namun, Islamic is integratif totality from â€œthree dâ€ : din (religion/science), daulah (state), and dunya (world). Islamic goverment system is a system that true different withÂ  the goverment system what ever in the world, a special system that unique among all system in the world. The authoritor power in islamic religion is itâ€™s self (khalifah fil ard) and the rule of syariah (al biladu biladullah wal ibadu ibadulloh). So, whoever wants to get happines and welfare (falah) in the world and in here after must be with Islamic from the creator of the world (Allah swt.)